Field pedological characterisation of two transects along the inner and outer sides of a sixty years old Tisza dike - a contribution to the problem of primary and secondary alkali grasslands - Tóth, Tibor; Langohr, Roger; Becze-Deák, Judit; Molnár, Zsolt (Acta Geographica Debrecina Landscape & Environment series, 2009)
Two transects were studied by field pedological investigations and soil bulk electrical conductivity measurements in order to understand the effect of a 60 year old dike along the Tisza River on soil formation and vegetation composition. There were no great differences in the soil properties. The soil is more saline and wetter inside the dike and vegetation reflected this environment. We hypothesize that the increasing build up of the riverbed might contribute to the contrast in soil and groundwater salinity between the area inside and the area outside the dike, similarly as conceptualised by Kuti (1989) for the Danube area, but at a much smaller distance.